INTEGRATION METHODS FOR DEVELOPING STUDENTS’ CREATIVE ACTIVITIES - Kalonova Farangiz Baxriddinovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores integration methods aimed at developing students’ creative activities in music education. It highlights pedagogical approaches that combine music with other art forms, interactive technologies, and project-based learning to enhance creativity, critical thinking, and artistic expression. The study emphasizes the importance of interdisciplinary strategies, collaborative projects, and multimedia tools in fostering students’ creative competencies and active participation in the learning process.